Indonesian EFL Learners’ Perceptions of Classroom Learning Environments in An EFL Context - Anggi Arigusman (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2017)
A good learning environment will determine the students’ learning quality. Therefore, creating supporting classroom learning environment is really crucial. This study explored the students’ perceptions at an Indonesian senior high school of actual classroom learning environment in English teaching across gender and grade. What Is Happening In this Classroom (WIHIC) questionnaire was applied to see the participants’ perceptions of the language learning environment. As for data analysis procedure, the scores obtained from the questionnaire were analyzed and described qualitatively. The data was examined to see how how is the students perception of their actual classroom learning environment in EFL classes across grade and gender. The result demonstrated similar perception indicated by five of the seven categories of the WIHIC questionnaire among grades. Across gender, four of the seven categories also indicated similar perception between male and female students where the categories get positively dominant result.